FOREIGN LANGUAGE LEARNING ANXIETY OF TURKISH CHILDREN AT DIFFERENT AGES - Sühendan Er (Informascope, 2015)
Although it is always under debate that anxiety has been experienced by most learners in the process of learning a foreign language, their culture is normally expected to help children avoid such a psychological risk in their language classes regardless of their age. In this study foreign language learning anxiety of Turkish children have been examined as a learning barrier. For the study both qualitative and quantitative data were collected from six EFL teachers and 544 students in randomly selected primary, secondary and high schools in Ankara. The Foreign Language Classroom Anxiety Scale (FLCAS), developed by Horwitz et.al. (1986), was administered as the data collection tool. The internal reliability achieved an alpha coefficient of 0.93 with all items producing significant corrected item total scale correlations and test- retest reliability over 8 weeks yielded the correlation coefficient 0.83(p<.0001). The results of the study revealed that as Turkish children get older, their level of anxiety rises too, and their culture of trust in their teachers and parents does not help them overcome this kind of a learning barrier.